A Comparative Study of Gen Z Consumer Behavior of Shopee Users in Surakarta - Fadilla Nur Aisyah; Ali Zainal Abidin (STIE Amkop Makassar, 2026)
This study aims to compare the level of consumptive behavior among Generation Z users of the Shopee application in Surakarta City based on their status as students, university students, and young workers. The rapid growth of the e-commerce, accompanied by the convenience of digital features scuh as free shipping, flash sales, product reviews, and digital payment systems, has driven changes in Generation’s consumption patterns. This research employed a descriptive quantitative approach with a purposive sampling technique involving 102 respondents, consisting of 34 high school, 34 university students, and 34 young workers. Data were collected through Likert-scale questionnaires and interviews, then analyzed using descriptive statistics with assistance of SPSS version 25. The results indicate differences in the level of consumptive behavior among the groups, where university students exhibit the highest average level of consumptive behavior, followed by young workers, while high school students show the lowest level. These differences are influenced by income level, lifestyle, and social environmental factors such as peer influence and social media. Furthermore, Shopee features that most influence purchasing decisions are product reviews and ratings, free shipping, and flash sales, while Shopee Live and PayLater show a more limited influence. Comparatively, this study demonstrates that generations Z’s consumptive behavior develops in line with changes in socio-economic status and the intensity of e-commerce platform usage.